Hypnotherapy is Needed to Reduce Online Gaming Addiction in Adolescence - Syari, Widya Rahma; Gusdiansyah, Edo; Welly (Journal of Health Sciences and Epidemiology, 2023)
Online game addiction has spread to be a widespread issue that impacts many people, especially adolescents. Adolescents with a gaming addiction impair their physical, mental, and social wellbeing and require treatment. Hypnotherapy is a cost-effective way to reduce online game addiction. This study aims to investigate the impact of hypnotherapy approaches on reducing online game addiction among adolescents. The research method used is a quasi-experimental, one-group pretest-posttest design. The study sample consisted of adolescents with severe online game addiction in the working area of the Kuranji Public Health Center, Padang City—as many as 20 adolescents. The sampling technique is purposive sampling. The data was analyzed using the Wilcoxon test, assisted by SPSS version 25. The results revealed that the average degree of online game addiction prior to receiving hypnotherapy was 55.55; however, after receiving hypnotherapy, the average value decreased to 42.45. The statistical results obtained have p values of 0.000. Hypnotherapy is recommended to be learned by every parent and teacher in order to control game addiction in their children. It is advised that parents of adolescent always supervise and instruct their children in proper behavior and establishing friends so as to prevent persistent online game addiction.